Structure-Based Optimization of 1,2,4-Triazole-3-Thione Derivatives: Improving Inhibition of NDM-/VIM-Type Metallo-β-Lactamases and Synergistic Activity on Resistant Bacteria - Matteo Bersani; Mariacristina Failla; Filippo Vascon; Eleonora Gianquinto; Laura Bertarini; Massimo Baroni; Gabriele Cruciani; Federica Verdirosa; Filomena Sannio; Jean-Denis Docquier; Laura Cendron; Francesca Spyrakis; et al. (MDPI AG, 2023)
The worldwide emergence and dissemination of Gram-negative bacteria expressing metallo-β-lactamases (MBLs) menace the efficacy of all β-lactam antibiotics, including carbapenems, a last-line treatment usually restricted to severe pneumonia and urinary tract infections. Nonetheless, no MBL inhibitor is yet available in therapy. We previously identified a series of 1,2,4-triazole-3-thione derivatives acting as micromolar inhibitors of MBLs in vitro, but devoid of synergistic activity in microbiological assays. Here, via a multidisciplinary approach, including molecular modelling, synthesis, enzymology, microbiology, and X-ray crystallography, we optimized this series of compounds and identified low micromolar inhibitors active against clinically relevant MBLs (NDM-1- and VIM-type). The best inhibitors increased, to a certain extent, the susceptibility of NDM-1- and VIM-4-producing clinical isolates to meropenem. X-ray structures of three selected inhibitors in complex with NDM-1 elucidated molecular recognition at the base of potency improvement, confirmed in silico predicted orientation, and will guide further development steps.